Monascus-fermented metabolites repressed amyloid β-peptide-induced neurotoxicity and inflammatory response in in vitro and in vivo studies. (May 2023) - Lin, Che-Wei; Lin, Pei-Ying; Hsu, Ya-Wen; Pan, Tzu-Ming; Lee, Chun-Lin
Graphical abstract: Highlights: MS and AK inhibited Aβ40-induced neurotoxicity in the in vitro and in vivo studies. MS and AK inhibited Aβ40-induced pro-inflammatory factors expressions. MS and AK inhibited Aβ40-induced neurotoxicity by antioxidative effects. MS and AK have more neuroprotection than donepezil. Abstract: Monascus purpureu s-produced monascin (MS) and ankaflavin (AK) have the potential to improve memory deficiency in Alzheimer's disease rat models; however, the mechanisms are still unclear. We aimed to investigate the effects and mechanisms of MS and AK on preventing Aβ40-induced oxidative stress and inflammatory response through in vitro and in vivo studies. Aβ40-treated PC-12 cells and intracerebroventricularly Aβ40-infused rats were used as the in vitro and in vivo models, respectively. MS and AK enhanced cell viability in Aβ40-treated PC-12 cells. Furthermore, the expression levels of oxidative and inflammatory factors, including COX-2, IL-1β, IL-6, iNOS, NF-κB, and TNF-α, were repressed by MS and AK treatment in the in vitro and in vivo models. The anti-oxidative and anti-inflammatory effects were the probable reasons for repressing Aβ40-induced p-tau protein expression, Aβ fibrils formation, neurotoxicity, and memory deficiency.